2007
DOI: 10.1038/sj.clpt.6100262
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Buprenorphine Analgesia with the Addition of Ultra-low-dose Naloxone in Healthy Subjects

Abstract: Animal studies have demonstrated that co-administration of an ultra-low-dose opioid antagonist with an opioid agonist may result in enhanced analgesia. Investigation of this effect in humans has been limited and produced inconsistent findings, with previous reports suggesting that dose ratio may be critical to analgesic potentiation. The aim of the current investigation was to determine whether buprenorphine analgesia could be enhanced with the addition of ultra-low-dose naloxone among healthy volunteers, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 40 publications
(46 reference statements)
1
22
0
Order By: Relevance
“…At ratios of 100:1, 133:1, and 200:1, changes in nociception were not statistically significant. These findings suggest that the enhanced antinociception previously described with the combination of buprenorphine and naloxone (La Vincente et al, 2008) may also be observed with naltrexone. Consistent with the naloxone study, this effect was dose-ratio dependent.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…At ratios of 100:1, 133:1, and 200:1, changes in nociception were not statistically significant. These findings suggest that the enhanced antinociception previously described with the combination of buprenorphine and naloxone (La Vincente et al, 2008) may also be observed with naltrexone. Consistent with the naloxone study, this effect was dose-ratio dependent.…”
Section: Discussionsupporting
confidence: 66%
“…A previous study with naloxone demonstrated that the ratio of agonist to antagonist was crucial to potentiation (La Vincente et al, 2008). Such ratios are likely to be different for the various antagonists given their different affinities for the μ‐opioid receptor.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…There was no analgesic benefit of adding naloxone to the PCA morphine solution (Sartain & Barry, 1999 Level II; Level II; Level II); in 'ultra low doses' but not in the higher dose studies, the incidence of nausea and pruritus was decreased Level II). In the experimental pain setting in volunteers, the coadministration of ultra-low doses of naloxone to patients given buprenorphine significantly increased tolerance to cold pressor pain (La Vincente et al, 2008 Level II). There is no information about the effect of naloxone in patients taking opioids in the longer term.…”
Section: Nmda and Opioid-receptor Antagonistsmentioning
confidence: 99%